2019
DOI: 10.1038/s41598-019-45014-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood pressure and risk of cancer development: a systematic review and meta-analysis of observational studies

Abstract: With the exception of renal cell carcinoma, studies assessing the association between hypertension and other cancers are inconsistent. We conducted a meta-analysis to assess this evidence. We included observational studies investigating the association between any definition of hypertension or systolic and diastolic blood pressure and risk of any cancer, after searching PubMed until November 2017. We calculated summary relative risks (RR) and 95% confidence intervals (CI) using inverse-variance weighted random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 177 publications
(129 reference statements)
7
110
5
3
Order By: Relevance
“…Alcohol intake has been associated with higher estradiol levels and higher mammographic density [12], and both pre-and postmenopausal breast cancer risk [13,14]. Recent meta-analysis observed a positive association between hypertension and breast cancer risk [15,16]. Moreover, a new cohort study reported a positive association between hypertension and breast cancer mortality after adjustments [17], supporting hypertension as an independent risk factor linked to breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol intake has been associated with higher estradiol levels and higher mammographic density [12], and both pre-and postmenopausal breast cancer risk [13,14]. Recent meta-analysis observed a positive association between hypertension and breast cancer risk [15,16]. Moreover, a new cohort study reported a positive association between hypertension and breast cancer mortality after adjustments [17], supporting hypertension as an independent risk factor linked to breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results from other large prospective studies reported positive associations of hypertension with the risk of cancers in locations other than the kidney in men (oropharynx, colon, rectum and anus, lung with larynx and trachea, bladder, malignant melanoma and non-melanoma skin cancer) 9 . The meta-analysis of four prospective studies between hypertension and esophageal adenocarcinoma yielded a statistically significant positive association 10 . Most recently, Christakoudi et al reported that there was a positive correlation between blood pressure and risk of esophageal carcinoma and head and neck cancers in a prospective European study 11 .…”
mentioning
confidence: 98%
“…It should be noted that in both the prior and the present investigations, 33 the age of patients at the time of diagnosis was markedly lower than that reported in the western countries, where it averages 70 years. 43,44 In addition to male sex and older age, family history of the disease, 45,46 diabetes, 47 hypertension, 48 inflammatory bowel disease, 49,50 smoking, 51 and alcohol abuse, 52 are often considered risk factors for colorectal cancer. In the population under study, the incidence of colorectal cancer was highest in subjects suffering from hypertension (33.33%) and diabetes (31.48%), reflecting the worldwide trends.…”
Section: Discussionmentioning
confidence: 99%